HUBUNGAN PENGETAHUAN DAN SIKAP REMAJA PUTRI DENGAN KEPATUHAN MENGKONSUMSI TABLET TAMBAH DARAH - Nana Aldriana; Mila Karmila; Heny Sepduwiana; Nina Surya Fitri Yanti (Maternity and Neonatal : Jurnal Kebidanan, 2025)
The iron tablets are iron folate tablets which each tablet contains 200 mg of Ferro Sulfate or 60 mg of elemental iron and 0.25 mg of folic acid. Adolescence is a period of transition from childhood to adulthood. At this time adolescents need sufficient nutritional needs to meet their needs. Because at this time the growth and development of adolescents is very fast. The most common nutritional problems in adolescents are energy and protein deficiency, anemia, and deficiencies of various vitamins and minerals. Young women are required to take Blood Supplement Tablets (TTD) because they experience menstrual cycles that come every month. This iron supplement is very useful in regenerating iron that has been lost due to menstruation and to meet the unmet need for iron from the food consumed daily. The purpose of this study was to determine the relationship between knowledge and attitudes of young women with adherence to consuming iron tablets at MAS Al-Fata Pasir Agung. This research method was carried out using a descriptive quantitative research type with an observation approach. The population and sample of this study were young women in grades X, XI and XII. Data analysis was performed univariately, bivariately with the chi-square test. The results of this chi-square study are the relationship between knowledge and compliance: Pvalue 0.0001 and OR=161.0 (95% CI=13.3-1943.2) and the relationship between attitude and compliance: Pvalue 0.0001 and OR=4.000 (95% CI=2.1-7.2). The conclusion in this study is that there is a significant relationship between knowledge and attitudes of young women with adherence to consuming Fe tablets. Suggestions for young women are expected to be more active in finding information about Fe tablets to increase knowledge, improve their attitude so that they are more obedient in consuming Fe tablets.